The Developing of Indonesian Teaching Materials For Foreign Speakers by Using Canva Media - Rahma Wati; Ernita Daulay (English Teaching and Linguistics Journal (ETLiJ), 2023)
This article is a development study that relies on some of the acquired literacy described. Using a qualitative descriptive approach. This discussion is about using the canva application as the Indonesian teaching media for foreign speakers. The learning media is indispensable to a teacher in sustaining and supporting teaching in education. The media is the tool teachers use in teaching, in addition to the use of books or methods of speaking, teachers are expected to have different learning mediums and adapt the materials and conditions to each student. At the present time, technological growth is accelerating, everyone is expected to understand the technology to support all activities it provides, as well as within the realm of education. Teachers and learners can utilize technology-based learning media one of them is a canva application. Canva is an online app that provides an intriguing design of the template, the features, and the categories given therein. With varied, intriguing designs, making the learning process is less boring. Using a canva application, learners can be easier to understand the material because it is presented with as attractive and easy-to-understand pictures or videos, to train both teacher and learner creativity, and skills to be acquired for learners so that this medium can also be used in the various spheres of life.